The Pedagogical Artefacts project. The toy as a pedagogical and artistic device from the avant-garde (Olhar de Professor, 2025)
The UVaMusEA project, made up of a team of 22 teachers from various disciplines and universities, museum professionals and students, develops its activity through specific projects with which we seek to meet the challenge of connecting future teachers with museums, participating in a learning community that acts inside and outside the university classroom. Artefactos Pedagógicos is one such project, inspired by the toys of the artistic avant-garde. It was developed with a group of students from the Primary Education Degree of the Faculty of Education and Social Work of the University of Valladolid. They designed artefacts halfway between an artistic piece and a pedagogical resource, as a mediation in the teaching and learning processes.
Keywords: Educational innovation; Museums; University